Studi Analisis Sistem Pendidikan Jenjang Sekolah Pertama di Singapura dan di Indonesia - Retno Susanti; Erna Retna Safitri; Fakhili Gulo; Anistasya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education is the foundation of nation development which is crucial in improving the quality of human resources (HR) and competitiveness in the era of globalization. This research compares the education systems of Indonesia and Singapore, which have significant differences in policies and outcomes. The method used is a literature study to analyze the challenges and advantages of the two systems. The research results show that Singapore has a structured and efficient education system, with a focus on the STEM curriculum and developing teacher quality. On the other hand, Indonesia faces the challenges of unequal access, disparities in quality between regions, and a curriculum that is less relevant. This research suggests the need for education reform in Indonesia by adopting best practices from Singapore, including improving teacher selection and training as well as infrastructure investment. Collaboration between government, educators and society is very important to realize quality and equitable education.